Lexical Transformations - Xolmo’minova Mahliyo Botirovna; Karimova O`g`iloy Rahmatullayevna; Borasulova Dilnoza Dilmurodovna (European Science Publishing, 2023)
As somebody who has been translating professionally for over 15 years now, I must confess the topic of Translation Techniques poses somewhat of a challenge; trying to pin down strategies that you use almost intuitively every day of your life becomes a rather difficult task. That is why I decided to outline a widely-accepted list of translation techniques in the hope that the reader may become interested in knowing a little bit more about translation and its nuances.
Keywords: Translation, lexical translation, substitution, modulation, generalization, differentiation.